BIAYA PRODUKSI DAN PAJAK PENGHASILAN ATAS LABA BERSIH PADA PERUSAHAAN MANUFAKTUR DI SUBSEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA (IDX) PADA TAHUN 2020-2022 - Agustiningsih, Maulina; Helmiati (Komunitas Manajemen Kompetitif, 2025)
This study aims to determine the effect of Production Costs and Income Tax on Manufacturing Companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange in 2020-2022. Sampling was carried out using a purposive sampling method of 18 companies in the Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange in 2020-2022. Data analysis was carried out using a multiple linear regression model. Based on the results of simultaneous tests of the Production Cost and Income Tax variables on Net Profit. Partially, Production Costs (0.950) have no effect on Net Profit. Partially, Income Tax (0.000) has an effect on Net Profit. The closeness of the relationship between the Production Cost and Income Tax variables on Net Profit is not strong with a correlation coefficient (R) obtained of (0.516). While the contribution of the independent variable to the dependent variable is 89.9% while the remaining 10.1% is influenced by other variables not examined in this study.